The Aetiology of Hand, Foot and Mouth Disease in Western Australia and the Northern Territory, 2007-2010 - Williams, David; Levy, Avram; Williams, Simon; Speers, David (International Union of Microbiological Societies, 2011)
Hand, foot and mouth disease (HFMD) is a common childhood disease characterized by fever and vesicular rash on the palms, feet, and buttocks, and oropharyngeal ulcers. HFMD is associated with infections by species A enteroviruses (EV). In rare cases, EV serotype 71 (EV71) infections are also associated with neurological disease. Surveillance of HFMD in Western Australia (WA) and the Northern Territory is undertaken routinely at PathWest Laboratory Medicine. Molecular testing involves initial screening using a RT-PCR targeting the 5'UTR of the EV genome. Amplicons are sequenced and their identities determined using BLAST. Where highest matches to EV71 or other EVs of interest are found, additional real-time RT-PCR and/or amplification and sequencing of partial VP1 gene is performed. The predominant serotypes associated with HFMD from January 2007 to December 2010 were EV71 and Coxsackievirus A6 (CAV6). For both serotypes, the majority of infections (74%) occurred in the <4 year age groups. Highest numbers of EV71 infections were found in 2009 (28 cases; with 26 occurring July to December), accounting for 29% of all EV infections detected July-December. Phylogenetic analyses of VP1 demonstrated co-circulation of B5 and C2 subgenogroups of EV71.The recent C2 strains showed closest genetic relationships to strains detected in Perth in 1999, suggesting continuous transmission of this lineage in WA. CAV6 emerged as a major cause of HFMD in WA and NT in 2010, with peak activity occurring from May-December (133 cases). CAV6 was the dominant EV serotype circulating during this time (65% of EVs detected). Phylogenetic analysis of partial VP1 identified three distinct lineages of CAV6, belonging to a single genogroup (G3), which includes emergent epidemic strains from Finland (2008), and indicates movement of this virus between Europe and WA. Interestingly, there was no evidence of onychomadesis (nail-shedding) following CAV6 infections, unlike in recent European epidemics.